KONTRIBUSI EFEKTIVITAS KOMUNIKASI UNTUK MENINGKATKAN KEPERCAYAAN NASABAH: Manajemen Pemasaran - Agustinus Philipus Peppy Fernandez, S.E.,M.Ec.Dev. (Ekonomedia, 2020)
In particular, customers in Bank Danamon Sukabumi Branch will have good confidence if the contribution of communication effectiveness provided by Bank Danamon Sukabumi Branch is good. Based on these thoughts, the writer is interested in examining the relationship between communication effectiveness and customer trust in Bank Danamon Sukabumi Branch. This research was conducted using descriptive associative analytic method which is describing the phenomena that occur during the study, then analyzed by linking one phenomenon to another. The population of this study is the total number of customers of Bank Danamon Sukabumi Branch who reside in the District of Cikole as many as 1,200 people, sampled using nonprobability techniques with judgment sampling with 120 customers being respondents. Data analysis using frequency analysis and correlation analysis to obtain the results of the study that is the relationship between the effectiveness of communication with customer trust in Bank Danamon Branch Sukabumi is shown by the magnitude of the correlation coefficient r = 0.551, the value is in the range 0.51-0.75 which means it has a fairly strong relationship , a positive relationship value which means that if the effectiveness of communication is getting better it will increase the level of customer confidence increasing.